ANALISIS TENTANG RENDAHNYA MINAT BELAJAR PESERTA DIDIK KELAS XI SMA NEGERI 5 PONTIANAK - Dewi Wiranda; Muhammad Asrori; Luhur Wicaksono (Universitas Tanjungpura, 2019)
AbstractThis research was about analysis extracurricular Islamic spiritual activity to developing students self-concept positive on eleventh grade at senior high school 1 Sungai Raya. The research problem in this study were “How is the activity of the extracurricular Islamic spiritual to developing students self-concept positive on eleventh grade at senior high school 1 Sungai Raya How is students self-concept on the eleventh grade at senior high school 1 sungai raya? the sub-problem were” what are the planning of the extracurricular Islamic spiritual to develoving students self-concept positive on the eleventh grade at senior high school 1 sungai raya? what are the stage of the extracurricular Islamic spiritual activity to developing students self-concept positive on the eleventh grade at senior high school 1 sungairaya?based on the research problem, this research aimed to describe” extracurricular activity Islamic philosophy to developing student self-concept on eleventh grad at senior high school 1 sungai raya. this resear used descriptive method with survey subject to choose the participant.this research was 40 students on eleventh grade. The method and tools of data collection used indirect communication techniques and questionair.Keywords: Extracurricular Islamic Spiritual Activity